Variation in Cell Number in a Population of Bembix Americana (Hymenoptera: Sphecidae) - John Alcock (Psyche: A Journal of Entomology)
This paper reports the results of observations made during the summers of 1971 and 1972 on a small group of Bembix americana Fabricius nesting in a vacant lot in Seattle, Washington. This population was judged to be intermediate to comata Parker and spinolae Lepeletier at the subspecific level (H. E. Evans, pers. comm.).